Enhancing Team Performance in Hybrid-Flexible Courses: The Role of Team Communication and Atmosphere - Wang, Miaohui; Zhan, Wei; Li, Yan; Song, Wu (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2025)
Hybrid-flexible (hyflex) courses have become a prominent open and distributed learning (ODL) approach post-COVID-19, offering students the flexibility to attend classes online, in-person, or both. While this model promotes instructional continuity and student-centered learning, it presents unique ODL challenges in managing effective team collaboration. This quantitative study investigated the underexplored relationships among effective communication, team atmosphere, and team performance in hyflex learning environments; the study sought to provide novel insights into optimizing team dynamics and enhancing learning outcomes in ODL-integrated educational settings. The study comprised data from 310 college students enrolled in the authors’ hyflex course offered on China’s Super Star learning platform at an ODL institution with over 700 million registered users. An online survey was conducted using validated scales; confirmatory factor analysis (CFA) and multiple linear regression analyses were used to test the hypotheses. The study found effective communication significantly enhanced team performance (β = 0.389, p < .001). Team atmosphere moderated this relationship (β = -0.118, p < .05); while a positive atmosphere generally supported performance, an overly positive one may have reduced the critical engagement necessary for optimal outcomes. The study concluded that both effective communication and a balanced team atmosphere were critical for maximizing team performance in hyflex courses. We suggest ODL educators foster communication strategies that encourage open dialogue and critical thinking while maintaining a supportive team environment. Overemphasis on maintaining positivity may hinder constructive critique and diminish performance in distance and hybrid settings.